Climate change and world heritage: a cross-border analysis of the Sundarbans (Bangladesh–India). Issue 2 (4th May 2019) - Hassan, Kamrul; Higham, James; Wooliscroft, Ben; Hopkins, Debbie
ABSTRACT: The national policy context influences micro-level management actions for natural World Heritage facing the challenge of climate change in the developing world. Little is currently known about how climate vulnerable natural World Heritage is managed to build resilience within the socio-ecological system. Management actions based on conservation, biodiversity, community and tourism policies are important determinants of socio-ecological resilience. The aim of this study is to present a critical cross-border comparative analysis of climate change management responses for building resilience in the Bangladesh and Indian Sundarbans World Heritage area. Drawing on semi-structured stakeholder interviews and document analysis, this research finds that along with the modification of conventional biodiversity conservation practices, management agencies address community needs such as adaptation, livelihoods, involvement and empowerment to build resilience by minimising community-induced forest depletion. The management regimes of the Sunderbans in Bangladesh and India have relative advantages in biodiversity conservation in response to climate change. This research also finds that biodiversity conservation actions are challenged by poor enforcement systems, destructive land use policy, and uncontrolled economic activities including tourism which may threaten the socio-ecological resilience of the World Heritage area.